Award for aspiring changemakers - Siti Nur Azwin, Zulkapri (The New Straits Times Press (M) Bhd., 2021)
A TOTAL of 11 graduates from the B40 community were bestowed the Pingat Tunku Award by the Tunku Abdul Rahman Foundation recently.